Kompetensi Literasi Digital Orang Tua dan Pola Pendampingan pada Anak dalam Pemanfaatan Media Digital - Wiratmo, Liliek Budiastuti (representamen, 2020)
Abstract The use of digital media is no longer dominated by adults. It has also become a part of children who are born as digital natives. This condition is certainly a challenge for parents because it is not possible to keep their children away from digital technology which offers various benefits. Therefore we need adults who are able to provide assistance to children in utilizing digital media. This article reveals how the patterns of parenting (in this case mothers) to children in utilizing digital media, what are the challenges faced and how to deal with these challenges. To answer this question, a qualitative descriptive approach was used. The informants who are the main data sources are working women and housewives who have children aged under five to 18 years, who are selected from the owners of active Facebook accounts (who in July uploaded their status, photos or other information). The findings of the study indicate that there are three patterns of mentoring, which were carried out by the informants, namely democratic-negotiation, permissive and protective. Parental Negotiative-Democratic Assistance allows the child to use the device, but there are negotiations, the child is invited to discuss, to determine when to hold the device, when to stop. Parental permissive assistance frees the child to use a device. Child protective assistance is given the opportunity to exist by having an Instagram account but is strictly controlled by parents. Key words: digital native, mentoring, digital media, digital literacy.